Cardiac Dedifferentiated Liposarcoma Requiring a Mitral Valve Replacement Complicated by Severe Paravalvular Leak: A Rare Case Report with Literature Review - Anju Adhikari; Adam Hafeez; Alexandra Halalau (Case Reports in Cardiology)
Cardiac sarcomas have a high infiltrative and metastatic potential and are often associated with poor prognosis. These tumors are often identified incidentally by thoracic and cardiac imaging. However, when symptomatic, their presentation can differ based on the localized structural effects on the endocardium, myocardium, pericardium, and valves as well as on dynamic effects on the cardiac function. We report a case of a 61-year-old female who presented to the emergency room with recurrent chest pain, fatigue, and chronic anemia. A transthoracic echocardiogram demonstrated a left atrial mass attached to the septal wall and anterior leaflet of the mitral valve. The mass was further characterized by a transesophageal echocardiogram and cardiac MRI. The patient underwent a resection of the left atrial mass with mitral valve replacement (MVR) and atrial septal defect repair. MVR was later complicated by paravalvular leak leading to acute congestive heart failure. Tissue immune histology was consistent with dedifferentiated liposarcoma. Cardiac dedifferentiated liposarcoma is extremely rare with only few cases reported in literature. We attempt to review the clinical features, diagnosis, and management of cardiac sarcoma with great emphasis.